2016
DOI: 10.1590/1983-21252016v29n118rc
|View full text |Cite
|
Sign up to set email alerts
|

Root Morphology and Nutrient Uptake Kinetics by Australian Cedar Clones

Abstract: -Evaluation of root morphology and kinetic parameters assist in the characterization of genotypes in nutrient uptake efficiency. This study characterized Australian cedar clones concerning their nutrient uptake capacity at the seedling stage through root morphology and the kinetics of P, K, Ca, and Mg uptake. The experiment was conducted using a nutrient solution in a greenhouse and growth chamber. Four Australian cedar clones (HE, XF, XD, and XE), provided by Bela Forest View (Empresa Florestal Bela Vista), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 19 publications
0
12
1
Order By: Relevance
“…Chen et al (2014aChen et al ( , 2014b reported that inoculation with endophytic bacterium Sphingomonas SaMR12 significantly improved the root length, root surface area, and average number of root tips in Sedum alfredii plant, as compared to uninoculated treatment. Batista et al (2016) suggested that root morphological parameters, such as total root length and root surface area, play an important role in nutrient uptake, particularly under micronutrient-limiting conditions.…”
Section: Modification In Root Morphology and Anatomymentioning
confidence: 99%
“…Chen et al (2014aChen et al ( , 2014b reported that inoculation with endophytic bacterium Sphingomonas SaMR12 significantly improved the root length, root surface area, and average number of root tips in Sedum alfredii plant, as compared to uninoculated treatment. Batista et al (2016) suggested that root morphological parameters, such as total root length and root surface area, play an important role in nutrient uptake, particularly under micronutrient-limiting conditions.…”
Section: Modification In Root Morphology and Anatomymentioning
confidence: 99%
“…Relationship between the values of available phosphorus in soil (mg kg -1 ) and P content in leaves (g kg -1 ) in crop season 2014/15 in Chardonnay (a) and Pinot Noir (b) subjected to application of increasing doses of P. * = significant at 5% probability. takes place primarily via diffusion to the roots (Dissanayaka et al, 2015, Batista et al, 2016. Thus we expect that a smaller amount of P is absorbed by grapevines, reducing photosynthesis, carbohydrate production, protein synthesis, and transfer and accumulation of energy, which are P-dependent functions in the plant (Brunetto et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…A higher number of leaves promote an increase in photosynthesis rate, entailing a bigger concentration of dry mass in aerial part (Table 1) (Figure 3), that way, a positive correlation between the parameters, as Table 4 shows. The growth of aerial part, occurred due to the higher concentrations of organic compounds in substrate, may influenced the development of roots (Figure 4), since the higher amount of light, proved by the correlation between the dry mass parameters (Table 4), allowed the seedling exploring the substrate in which were inserted, guarantying a greater assimilation of nutrients (MONTEIRO NETO et al, 2016;BATISTA et al, 2016).…”
Section: Discussionmentioning
confidence: 99%